Permeability Correction Method of Sandy Conglomerate Reservoir Based on Flow Unit Division - MAO Chenfei; GAO Yanwu; XIAO Hua; CHEN Guojun; LIU Haiming; WU Wei; GAO Ming (Cejing jishu)
In sandy conglomerate reservoir, the contents of gravel, sand and shale components change rapidly, the pore throat structure is complex, and the calculation error of permeability is big. In order to improve the permeability calculation accuracy of this kind of reservoir, based on the analysis of the main controlling factors of permeability, it’s clarified that pore structure and clay content are important influencing factors of permeability in the Wuerhe formation in Dinan salient, Junggar basin. The permeability calculation model is established by the flow unit division to eliminate the influence of pore structure on permeability. According to the fluid seepage theory and the physical model of rock capillary, the permeability model considering the influence of clay in pores is deduced. Then the calculation model of clay content in pores is established by logging curve combination method, so as to obtain the final permeability model after clay content correction. The results show that the permeability model with comprehensive flow unit division and clay content correction has higher calculation accuracy, smaller relative error and better agreement with experimental data. This model can effectively improve the calculation accuracy of permeability of sand-conglomerate reservoirs.